Arbitrarily High-Order Energy-Conserving Methods for Hamiltonian Problems with Quadratic Holonomic Constraints (Journal of Computational Mathematics, 2024)
In this paper, we define arbitrarily high-order energy-conserving methods for Hamiltonian systems with quadratic holonomic constraints. The derivation of the methods is madewithin the so-called line integral framework. Numerical tests to illustrate the theoreticalfindings are presented.
Keywords: Constrained Hamiltonian systems; Quadratic holonomic constraints; Energy-conserving methods; Line integral methods; Hamiltonian Boundary Value Methods; HBVMs.